2012
DOI: 10.1177/0961203312448105
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus versus cyclophosphamide as treatment for diffuse proliferative or membranous lupus nephritis: a non-randomized prospective cohort study

Abstract: Treatment of lupus nephritis (LN) with cyclophosphamide (CYC) is effective but retains a certain severe adverse effect. Tacrolimus (TAC) may be a suitable treatment for LN. Forty patients with diffuse proliferative or membranous LN were recruited for this non-randomized open-label study - 67.5% (27/40) had nephrotic proteinuria (>3.5 g/day) and 50.0% (20/40) had low estimated glomerular filtration rate (eGFR) (<60 mL/min/1.73m(2)). We compared the efficacy and adverse effects of TAC (0.04-0.08 mg/kg/d)/prednis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
3
38
0
1
Order By: Relevance
“…These drugs not only bind to P-gp and inhibit its activity but also downregulate P-gp expression by inhibiting IL-2 synthesis. Recently, few studies and even a meta-analysis have highlighted the efficacy of tacrolimus in proliferative lupus nephritis and reported its superiority over CYC in induction and even during maintenance therapy [35][36][37][38][39][40]. Another recent study, in which CYC refractory lupus nephritis patients have been effectively treated with low-dose tacrolimus [41], gives strength to our concept to use specific P-gp inhibitors.…”
Section: Discussionmentioning
confidence: 88%
“…These drugs not only bind to P-gp and inhibit its activity but also downregulate P-gp expression by inhibiting IL-2 synthesis. Recently, few studies and even a meta-analysis have highlighted the efficacy of tacrolimus in proliferative lupus nephritis and reported its superiority over CYC in induction and even during maintenance therapy [35][36][37][38][39][40]. Another recent study, in which CYC refractory lupus nephritis patients have been effectively treated with low-dose tacrolimus [41], gives strength to our concept to use specific P-gp inhibitors.…”
Section: Discussionmentioning
confidence: 88%
“…However, eight of the 17 studies were excluded because they contained duplicate data, [25][26][27] non-RCT data, [28][29][30] or no outcome data. 31 Figure 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The efficacy of tacrolimus for LN was established in a randomized con- trolled trial conducted in Japan (10) and confirmed in a systematic review (11). In addition, tacrolimus has been reported to be safer than IVCY (12). We herein report a case of refractory LN that was successfully treated with a combination of tacrolimus and IVCY, despite neither of these agents demonstrating any efficacy when administered separately.…”
Section: Introductionmentioning
confidence: 61%